2003
DOI: 10.1590/s0102-76382003000300007
|View full text |Cite
|
Sign up to set email alerts
|

Cardioplegia using low volumic cardioplegic agents: morphological study in isolated rabbit hearts

Abstract: AbstractsIntroduction: Pharmacological cardioplegic solution aims to eliminate the consequences of ischemic damage, which results from the misbalance between the offer and consumption of energy during the arrest of the heart beats during cardiac surgery with cardiopulmonary bypass.Objectives: This research experimentally evaluates the structural and ultrastructural changes in isolated rabbit hearts submitted to arrest protected by a Low Volumetric Cardioplegic Solution (LVCS).Material and Method: The study cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The low potassium concentration associated to magnesium in blood cardioplegia (Group I), permitted arrest of the heartbeats and a reduction in energy consumption during the induction period. Moreover, with continuous perfusion of oxygen supplied by the blood of the donor rabbit at 37ºC, ischemia was avoided and the aortic clamping could be considered a period of heart reserve maintenance rather than a period of ischemic damage [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low potassium concentration associated to magnesium in blood cardioplegia (Group I), permitted arrest of the heartbeats and a reduction in energy consumption during the induction period. Moreover, with continuous perfusion of oxygen supplied by the blood of the donor rabbit at 37ºC, ischemia was avoided and the aortic clamping could be considered a period of heart reserve maintenance rather than a period of ischemic damage [13].…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of ATP at the end of the ischemic period also has a direct relationship with the degree of functional recovery of the myocardium. Lima-Oliveira et al [13] demonstrated experimentally that low-volume blood cardioplegia was efficient to maintain the myocardial cells, fibroblasts and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation